2019
DOI: 10.1074/jbc.ra119.010676
|View full text |Cite
|
Sign up to set email alerts
|

Non-templated addition and template switching by Moloney murine leukemia virus (MMLV)-based reverse transcriptases co-occur and compete with each other

Abstract: Single-cell RNA-Seq (scRNA-Seq) has led to an unprecedented understanding of gene expression and regulation in individual cells. Many scRNA-Seq approaches rely upon the template switching property of Moloney murine leukemia virus (MMLV)-type reverse transcriptases. Template switching is believed to happen in a sequential process involving nontemplated addition of three protruding nucleotides (+CCC) to the 3′-end of the nascent cDNA, which can then anneal to the matching rGrGrG 3′-end of the template-switching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 41 publications
(55 reference statements)
3
75
0
Order By: Relevance
“…The RAMPAGE protocol preserves the mRNA polarity in the resulting cDNA library by the directed introduction of Illumina-sequencing adapters for Read 1 at the 5′ end via a template switching oligo (TSO), and for Read 2 toward the 3′ end of the mRNA transcript via a randomly-priming reverse-transcription (RT) primer ( Figure 1A , panel 3 ). RAMPAGE employs two approaches to enrich for 5′-intact mRNA based on the presence of the 5′-m7G cap structure (cap): by (1) introducing the 5′-sequencing adapter via template switching, which preferentially occurs at the cap ( Wulf et al., 2019 ), and by (2) biotinylation of the cap, followed by capture on streptavidin-coated beads ( Figure 1A , panels 3–5 ). Upon library amplification and paired-end sequencing, reads from both replicates of all three samples were mapped to the ME49 genome assembly (ToxoDB, version 45), and reads originating from ribosomal RNA (rRNA) contamination were removed ( Figure 1A , panels 6–8; Figure 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…The RAMPAGE protocol preserves the mRNA polarity in the resulting cDNA library by the directed introduction of Illumina-sequencing adapters for Read 1 at the 5′ end via a template switching oligo (TSO), and for Read 2 toward the 3′ end of the mRNA transcript via a randomly-priming reverse-transcription (RT) primer ( Figure 1A , panel 3 ). RAMPAGE employs two approaches to enrich for 5′-intact mRNA based on the presence of the 5′-m7G cap structure (cap): by (1) introducing the 5′-sequencing adapter via template switching, which preferentially occurs at the cap ( Wulf et al., 2019 ), and by (2) biotinylation of the cap, followed by capture on streptavidin-coated beads ( Figure 1A , panels 3–5 ). Upon library amplification and paired-end sequencing, reads from both replicates of all three samples were mapped to the ME49 genome assembly (ToxoDB, version 45), and reads originating from ribosomal RNA (rRNA) contamination were removed ( Figure 1A , panels 6–8; Figure 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…We generated a comprehensive full-length transcript database in B. napus by pooling RNA from five tissues with four cDNA libraries with sizes ranging from < 1 kb to > 3 kb using the PacBio Iso-Seq approach. Recently, it has been reported that template switching take place in a sequential process, allowing the reverse transcriptase (RT) to switch templates and continue copying the templateswitching oligo sequence (Wulf et al, 2019). Moreover, the presence of a 5 0 cap can enhance template switching efficiency, allowing cDNAs from uncapped RNA to also be tagged with a 5 0 adapter sequence.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…The SMARTer small RNA kit (Takara) uses poly-adenylation followed by reverse transcription and template switching to make ligation-free libraries. While this technique does eliminate ligation associated biases, template switching on uncapped sRNAs itself has some sequence bias ( 17 ). Furthermore, for reasons that are not well understood, template switching has a very low detection sensitivity for miRNAs compared to ligation-based approaches when performed on total RNA, due to a large amplification of background RNA such as rRNA ( 18–20 ).…”
Section: Introductionmentioning
confidence: 99%